JATIBARANG LANDFILL OF SEMARANG CITY: IS IT POTENTIAL AS THE WATER CONTAMINATION SOURCE? - Heru Hendrayana; Doni Prakasa Eka Putra; Thomas T. Putranto; Ponhalath Xaixongdeth (Journal of Applied Geology, 2015)
Like other million inhabitants Cities, Semarang which is the capital city of Central Java Province in Indonesia has a problem in solid waste management. One biggest landfill in the City is the Jatibarang Landfill. The landfill operated since 1992 and currently receives the domestic waste of about 337 ton/day with total volume of about 5.2 million m3 of solid waste. It located on the hill slope of sandstone tertiary rocks and relatively closed to the river of Kreo (which is the main source of drinking water for Semarang City). In order to evaluate the potentiality of landfill as the contamination source to groundwater and surface water, the quality of leachates were analyzed and the hydrogeology of the area was re-studied. Result of the study show that the leachates contain high chloride concentration of about 2600 mg/L however low concentration of heavymetals. Hydrogeology study show evidence that this leachate is already enters the groundwater system. However its load to the river can be neglected due to the fact that the chloride mass flux derived from the study area was significantly low comparing to the net river loads. Key Word: landfill, water contamination, chloride, groundwater and surface water interaction